UMP going greener MoU with Greentech Malaysia - UMP, PNC (2018)
A Memorandum of Understanding (MoU) between Universiti Malaysia Pahang (UMP) and Malaysian Green Technology Corporation (GreenTech Malaysia) was inked currently, to collaborate and promote effort in research cooperation in the development of green technology policy, management and the industry 4.0.